Public awareness, news promptness and the measles outbreak in Hong Kong from March to April, 2019. Issue 4 (2nd April 2020) - Zhao, Shi; Han, Lefei; He, Daihai; Qin, Jing
Abstract: Background: Globally, a resurgence of measles during the last decade may be attributed to many factors. An unexpected measles outbreak occurred in Hong Kong, and infected 29 airport staff between March and April 2019. The authority updated public on new cases daily, a public enquiry telephone/online platform was set up on March 23, and an emergent vaccination programme was launched targeting unvaccinated airport staff. We aimed to study this measles outbreak and its related factors. Methods: We quantified the transmissibility of the outbreak by the time-varying effective reproduction number, R eff ( t ), and inferred the time-varying basic reproduction number, R 0 ( t ). We examined the statistical associations between local public awareness or reporting delay and the R 0 ( t ). Results: Our estimated average R 0 is 10.7 with 95% CI of 6.0–29.2. We found that R 0 ( t ) was negatively associated with the level of public awareness and the level of promptness of situation updates on new cases. Conclusion: Public awareness via situation updates helped to control the outbreak. The medical effects of the vaccination programme was not soon enough to cause the immediate shutting down of the outbreak, but it boosted herd immunity to prevent future airport outbreaks in the next few years.